Immunogenicity and Safety of BNT162b2 Homologous Booster Vaccination in People Living with HIV under Effective cART - Laura Gianserra; Maria Gabriella Donà; Eugenia Giuliani; Christof Stingone; Martina Pontone; Anna Rita Buonomini; Massimo Giuliani; Fulvia Pimpinelli; Aldo Morrone; Alessandra Latini (Vaccines, 2022)
Data on COVID-19 boosting vaccination in people living with HIV (PLWH) are scant. We investigated the immunogenicity and safety of the BNT162b2 homologous boosting vaccination. Anti-SARS-CoV-2 spike antibodies (LIAISON® SARS-CoV-2 S1/S2 IgG test, DiaSorin®), CD4+, CD8+ and viraemia were monitored at T0 (pre-vaccination), T1 (4 weeks after the second dose), T2 (pre-booster) and T3 (4 weeks after the booster dose). Humoral responses were evaluated according to sex, age, BMI, nadir and baseline CD4+ counts, as well as type of cART regimen. Forty-two subjects were included: the median age was 53 years (IQR: 48–61); the median time since HIV was 12.4 years (IQR: 6.5–18.3); the median nadir and baseline CD4+ counts were 165 (IQR: 104–291) and 687 cells/mm3 (IQR: 488–929), respectively. The booster dose was administered at a median of 5.5 months after the second dose. Median anti-SARS-CoV-2 IgG concentration had significantly decreased at T2 compared to T1 (107 vs. 377, p < 0.0001). Antibody levels elicited by the booster dose (median: 1580 AU/mL) were significantly higher compared with those of all the other time points (p < 0.0001). None of the investigated variables significantly affected antibody response induced by the booster dose. Local and systemic side-effects were referred by 23.8% and 14.3% of the subjects, respectively. One patient developed sensorineural hearing loss (SNHL) 24 h after boosting. He recovered auditory function upon endothympanic administration of corticosteroids. The BNT162b2 boosting vaccination in PLWH is safe and greatly increased the immune response with respect to the primary vaccination.